2021
DOI: 10.3390/hydrology8010039
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Irrigation Water Use Efficiency for Tomato and Maize Fields across Italy Combining Remote Sensing Data and the AquaCrop Model

Abstract: Remote sensing data of canopy cover and leaf area index are used together with the AquaCrop model to optimize irrigation water use efficiency for tomato and maize fields across Italy, which differ in climate, soil types and irrigation technique. An optimization irrigation strategy, “SIM strategy”, is developed based on crop stress thresholds and then applied to all the analyzed fields in different crop seasons, evaluating the effect not only on irrigation volume and number of irrigations but also on crop yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 57 publications
3
6
0
Order By: Relevance
“…Rinaldi et al [22] also found weaker relative RMSE results for dry yields compared to total dry matter. The modelled fresh yield of tomato was comparable to the observed one with an error of 9% in the calibration process [37]. We found lower errors in final yields, from 1.2% to 5.5%, depending on the water supply.…”
Section: Simulation Of Biomass and Yield In The Growing Seasonsupporting
confidence: 77%
“…Rinaldi et al [22] also found weaker relative RMSE results for dry yields compared to total dry matter. The modelled fresh yield of tomato was comparable to the observed one with an error of 9% in the calibration process [37]. We found lower errors in final yields, from 1.2% to 5.5%, depending on the water supply.…”
Section: Simulation Of Biomass and Yield In The Growing Seasonsupporting
confidence: 77%
“…This shows that applying stage deficit irrigation improves yield and water productivity compared to FI [4]. This result is also confirmed by [22,24,47,48,49,50]; the best WP was observed at the lowest irrigation depth.…”
Section: Statically Validation Performance Of Aquacropsupporting
confidence: 57%
“…Additionally, studies have shown that the model accurately simulates the yields and water requirements of various crops grown worldwide [15][16][17][18][19]. AquaCrop can also be used effectively to predict crop water requirements by assimilating the canopy cover estimated from Sentinel-2 imagery [20][21][22][23], and to evaluate the effects of optimized irrigation management on the minimization of percolation losses and maximization of crop yield for different soil types [24].…”
Section: Introductionmentioning
confidence: 99%